2013
DOI: 10.1016/j.scitotenv.2012.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between pH and nutrients on benthic algae in streams and consequences for ecological status assessment and species richness patterns

Abstract: Eutrophication and acidification are among the major stressors on freshwater ecosystems in northern Europe and North America, but possible consequences of interactions between pH and nutrients on ecological status assessment and species richness patterns have not previously been assessed. Using data from 52 river sites throughout Norway, we investigated the combined effects of pH and nutrients on benthic algae assemblages, specifically 1) taxaspecific couplings between nutrient and acidity traits, 2) the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 61 publications
6
42
0
Order By: Relevance
“…The relationship between diatom diversity metrics and productivity has remained unclear either because of complex environmental influences or because other variables than nutrients determine diatom diversity (Soininen, 2009). Archibald (1972) found linear negative and Lavoie et al (2008) found positive relationships between diversity and nutrients, Schneider et al (2013) between species richness and nutrient (TP), while Bellinger et al (2006) did not find any significant patterns between them, similar to our results. This is the reason why some authors did not suggest these indices for evaluating ecological conditions (Blanco et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relationship between diatom diversity metrics and productivity has remained unclear either because of complex environmental influences or because other variables than nutrients determine diatom diversity (Soininen, 2009). Archibald (1972) found linear negative and Lavoie et al (2008) found positive relationships between diversity and nutrients, Schneider et al (2013) between species richness and nutrient (TP), while Bellinger et al (2006) did not find any significant patterns between them, similar to our results. This is the reason why some authors did not suggest these indices for evaluating ecological conditions (Blanco et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…3 A self- percent organic matter, and chlorophyll showed a clear, significant increase with the stream order until the sixth-order streams and then slightly decreased (Naiman, 1983). Diatom species and genus number showed hump-shaped pattern along the pH (Schneider et al, 2013). Neither the above pattern nor the humped-shaped relationship appeared in case of benthic diatoms along stream order in the study of Minshall et al (1983).…”
Section: Discussionmentioning
confidence: 78%
“…1a). Schneider et al (2013) demonstrate the problems of evaluating nutrient status in the presence of a strong acid pressure and although this paper deals with rivers rather than lakes, the principles should be transferable. Juggins (2013) points out other issues associated with interpretation of univariate responses in the presence of confounding variables.…”
Section: Response Of Diatoms In Low Alkalinity Lakesmentioning
confidence: 99%
“…Some of these studies (e.g., Lavoie et al, 2004;Kelly et al, 2008;Potapova and Carlisle, 2011) contribute to the impression that soft-bodied algae did not improve stressor responsiveness of diatoms alone, but they were based on taxonomy methods that allowed mainly genus-level or coarser identifications of soft-bodied algae which may account for the conclusions. In contrast, studies designed to explore the full potential of soft-bodied algae demonstrated that they enhance bioassessment power along the following lines of consideration: (1) multimetric indices based on entire algal communities, created in southern Californian streams, showed better responsiveness to anthropogenic stress over indices based either on diatoms or soft-bodied algae assemblages alone (Fetscher et al, 2014); (2) the best performing softbodied algal index exhibited greater discriminatory power than its diatom counterpart near the higher end of the range of anthropogenic disturbance (Fetscher et al, 2014); (3) differences in diatom and soft-bodied algal biotic indices were detected in ecosystems which are subject to changing environmental conditions; these differences could provide indications related to ecosystem stability (Schneider et al, 2012); (4) diatom and soft-bodied algal communities respond to nutrient supply and pH differently, with diatom taxon richness generally increasing with nutrient availability in contrast to decreasing soft-bodied algae richness (Schneider et al, 2013); (5) diatoms in conjunction with soft-bodied algae provide a more robust assessment of nutrient conditions, inferring nitrogen (N) limitation in 20% more sites than monitoring with either algal group alone (Stancheva et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%